Analysis of Readiness to Use the Metaverse Platform in Learning Activities - Yohannes Kurniawan; Aldino E. Susandyoga; Irfan A. Kamal; Raditya Sismandrajaya; Siti Elda Hiererra; Ganesh Bhutkar (Ital Publication, 2023)
Metaverse technology is one of the many technological breakthroughs in education, notably in the teaching and learning process in the classroom, especially since the COVID-19 epidemic. This study aims to investigate, model, and assess the potential adoption of metaverse technology from the viewpoint of BINUS University students. The study methodology that is employed is quantitative descriptive analysis. This research used Mozilla Hub's SPOKE to create the classroom simulation. Students are asked to use a laptop web browser and a Virtual Reality (VR) headset to replicate two scenarios from the metaverse realm. The variables used are comfort, convenience, compatibility, interest, and efficacy. The findings of this research indicate that a more significant number of participants, as much as 80% than fewer respondents (20%) were interested in employing VR (the Metaverse) for online teaching and learning using headsets. The novelty in this research is that academics can find out student behavior that they prefer to study using a VR headset compared to a regular laptop by opening a web browser. This can be a special note that the use of VR headsets in learning can increase interest in learning so that it is more effective in providing teaching material. Future work for this study is the application of this metaverse technology, which still requires work and development, as it still necessitates careful planning and consideration of a few factors, including security, infrastructure availability, and user comfort. Doi: 10.28991/ESJ-2023-07-06-016 Full Text: PDF